Environmental maternal exposures and the risk of premature birth and intrauterine growth restriction: The Generation Gemelli study protocol of newborn exposome. - Leonardo Villani; Angelo Maria Pezzullo; Roberta Pastorino; Alessandra Maio; Francesca Stollagli; Chiara Tirone; Marta Barba; Angela Maria Cozzolino; Denise Pires Marafon; Martina Porcelli; Annamaria Sbordone; Maria Letizia Patti; et al. (PLoS ONE)
Background The study of women exposures and child outcomes occurring in the first 1,000 days of life since conception enhances understanding of the relationships between environmental factors, epigenetic changes, and disease development, extending beyond childhood and spanning the entire lifespan. Generation Gemelli is a recently launched case-control study that enrolls mother-newborns pairs in one of the largest university hospitals in Italy, in order to examine the association between maternal environmental exposures and intrauterine growth restriction (IUGR) and the risk of premature birth. The study will also evaluate the association of maternal exposures and the health and growth of infants and children up to 24 months of age. Methods The study entails the set-up of a case-control study within a birth cohort. With approximately 4,000 annual deliveries, we aim to enroll 140 cases (newborns with IUGR and premature birth) and 280 controls per year, from September 2022. A comprehensive questionnaire will be used to gather information about various types of maternal environmental exposures before and during pregnancy. We will collect biological samples from both mothers and newborns (including vaginal swab, placenta sample, blood, saliva, meconium, and bronchoalveolar lavage fluid) at birth and within the early hours of the newborn's life. We will perform laboratory examinations including dosage of heavy metals and essential elements, investigation of placental distress and fetal brain damage of biomarkers, analysis of microbiota and of DNA methylation profile. We will conduct clinical follow-up assessments in both cases and controls at months 12 and 24 and we will collect anthropometric data, feeding types with particular reference to breastfeeding and its duration, pediatric emergency room visits, hospitalizations, medication usage, known allergies, and neuropsychological development. Discussion The Generation Gemelli case-control study holds the promise of significantly enhancing our comprehension of how maternal environmental exposures relate to the health of children and the broader population. The study of the exposome will provide insights into the relationships between environmental exposures, epigenetic changes and health outcomes during the first 1000 days of life and onward.